Promoting Children’s Language Learning Through Digital-Based Literacy - Rauf Babafemi Adetokun; Oluwaseyi Funmi Omotayo; Kehinde Omotayo; Anuoluwapo Okanlawon (EduLine: Journal of Education and Learning Innovation, 2023)
Technology is constantly changing the world to a place driven by ICT and increasingly making high numbers of the 21st century children a set of digital natives. Despite children’s exposure to the digital world and strong policy provisions on ICT in education, language teachers are yet to fully leverage on the importance of technology in teaching and learning particularly at the primary school level. This study, therefore, investigated how children’s language learning has been improved through digital-based literacy. It discussed the relevance of digital-based teaching as against the chalk and talk method wrapped with memorization, repetition and note-copying. The study hung on two theories; Technology Acceptance Model 2 and Uses and Gratifications Theory. It utilized historical research by exploring literature in the library, on the internet and other secondary sources to collect data which was analyzed using content analysis. The study revealed that technology supports manifestation of child-centred teaching and learning situations which in turn makes pupils to explore, observe, engage and solve language related problems independently. The study concluded that even though the influx of technology enhances effectiveness in language learning; teachers still remain the pillar for quality instruction in education. It then recommended that teachers must be trained and supported in using technological devices while teaching and pupils must be exposed to only educative media content while learning.